2019
DOI: 10.4336/2019.pfb.39e201701550
|View full text |Cite
|
Sign up to set email alerts
|

Shoot multiplication of two <em>Sequoia sempervirens </em> genotypes with addition of small concentrations of kinetin

Abstract: Sequoia sempervirens (D. Don) Endl. é uma conífera que produz madeira de elevada qualidade, com potencial de aplicação na indústria. No entanto, a espécie exibe baixas taxas de germinação. Este estudo foi dedicado à otimizar um protocolo para a multiplicação de brotos de S. sempervirens, através da micropropagação. Dois genótipos, adaptados ao Sul do Brasil, foram a fonte de explantes para o estudo da multiplicação in vitro. Utilizou-se o meio de cultura MS (Murashige Skoog) (50% de sua concentração original) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
1
2
0
1
Order By: Relevance
“…In this study, the shoot induction, the number of shoots per explant, the root induction, and the number of roots per explant were affected by the explant's genotype. Our results are in concordance with the results reported by Meneguzzi et al 2 , who observed different genotypes' responses in shoot multiplication of S. sempervirens. Similarly, Sul and Korban 14 found differences in shoot proliferation and shoot elongation of S. sempervirens.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In this study, the shoot induction, the number of shoots per explant, the root induction, and the number of roots per explant were affected by the explant's genotype. Our results are in concordance with the results reported by Meneguzzi et al 2 , who observed different genotypes' responses in shoot multiplication of S. sempervirens. Similarly, Sul and Korban 14 found differences in shoot proliferation and shoot elongation of S. sempervirens.…”
Section: Discussionsupporting
confidence: 94%
“…Endl. (Taxodiaceae) is a valuable forest species and occurs naturally in Western North America, especially in California 1,2 . This species is the tallest tree on earth with a high volume of standing biomass, in some stands exceeding 3500 metric tons/hectare 3 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations